The Effect of Homogeneity Psycho Cognition Strategies on Students' Understanding of Physics Concepts in Static Fluid Topics (Department of Physics, Faculty of Mathematics and Natural Sciences, 2023)
Students' difficulties related to the concepts underlying the static fluid phenomenon are still lacking serious attention from physics education researchers. This study aims to increase students' understanding of physical concepts in solving conceptual problems related to static fluid phenomena using the Homogeneity Psycho Cognition (HPC) strategy. The analysis was carried out based on student answers to brief description questions and the level of student confidence in the accuracy of the answers. The results of the study show that the HPC strategy can improve students' understanding of concepts. At the initial meeting the students did not understand well and even indicated they had misconceptions. However, after carrying out the learning process, the results of students' understanding of concepts at each meeting are increasing. The increase in students' understanding of physics concepts with the HPC strategy is higher than the increase in students with teacher-centered or conventional learning. Thus, HPC can be recommended to improve students' understanding of physics